Peran Website dalam Penyebaran Hadis di Era Digital - Hamid, Abdul (Prodi Ilmu Hadis Fakultas Ushuluddin dan Dakwah Institut Agama Islam Negeri Madura, 2024)
This study explores the impact of digitalization on hadith scholarship, particularly the role of websites in the dissemination and study of hadith in the modern era. Digitalization has significantly improved access to hadith sources, enabling the global transmission of Islamic teachings. However, it also presents challenges related to data authenticity, textual variations, and shifts in scholarly authority within Islamic studies. Employing a literature-based qualitative approach, this research analyzes various digital platforms that support hadith scholarship, including Waqfeya, Dorar.net, CariHadis.com, and Hadis Digital Online All in One, which serve as repositories providing access to hadith texts and related references. The findings indicate that digitalization facilitates hadith retrieval, fosters academic research, and enhances the integration of technology into Islamic studies. However, concerns over data integrity, textual accuracy, and scholarly credibility remain significant. While digital platforms offer unprecedented access to hadith, the lack of standardized validation methods raises the risk of misinformation and misinterpretation. Therefore, this study highlights the necessity of establishing rigorous validation standards and adopting reliable verification mechanisms to maintain the credibility and scholarly integrity of digital hadith resources. Strengthening digital literacy and scholarly oversight is essential to ensure that digital platforms serve as accurate and authoritative sources for hadith studies. This research contributes to the ongoing discourse on the intersection of technology and Islamic scholarship, emphasizing the importance of maintaining academic rigor in the digital transmission of hadith